Do Europeans Care about Climate Change? An Illustration of the Importance of Data on Human Feelings - Adam Nowakowski; Andrew J. Oswald (Institute of Labor Economics (IZA), 2020)
Economists have proposed a variety of sophisticated climate-change interventions. But do our citizens care enough about climate change to enact such policies? This paper provides evidence that suggests they do not. Two kinds of findings are presented. Using data on 40,000 Europeans from the 2016 European Social Survey, the paper shows that only 5% of people say they are extremely worried about climate change. The cooler European countries express particularly low levels of worry. Using data on 30,000 citizens from the 2019 Eurobarometer Surveys, the paper demonstrates that climate change is viewed as a less important problem than parochial issues such as (i) health and social security, (ii) inflation, (iii) unemployment, and (iv) the economic situation. Other results, from regression equations, are provided. This paper's conclusions seem to have exceptionally serious implications for our unborn great grandchildren – and imply that economic policy should now focus on how to alter feelings rather than upon the design of complicated theoretical interventions. An analogy with successful anti-tobacco policy is discussed.
Keywords: Q54; Q58; 330; climate change; global warming; feelings; economic policy; welfare